A statistical equilibrium approach to Adam Smith's labor theory of value - Ellis Scharfenaker; Bruno Miller Theodosio; Duncan K. Foley (The University of Utah, Department of Economics, 2024)
Adam Smith's inquiry into the emergence and stability of the self-organization of the division of labor in commodity exchange is considered using statistical equilibrium methods from statistical physics. We develop a statistical equilibrium model of the distribution of independent direct producers in a hub-and-spoke framework that predicts both the center of gravity of producers across lines of production as well as the endogenous fluctuations between lines of production that arise from Smith's concept of "perfect liberty". The ergodic distribution of producers implies a long-run balancing of "advantages to disadvantages" across lines of employment and gravitation of market prices around Smith's natural prices.
Keywords: 330; Competition; Hub-and-spoke; Value theory; Classical Political Economy; Statistical equilibrium